Self-driven condensation-enhanced surface based on pyroelectric effect and preparation method thereof
Patent Information
- Application Number
- CN202611139094.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-13
AI Technical Summary
[0008]本发明的目的在于针对现有滴状冷凝强化技术中主动驱动方式依赖外部能源输入、系统结构复杂以及被动驱动方式在冷凝初期存在驱动力不足等问题,提供一种基于热释电效应的自驱动冷凝强化表面及其制备方法
1)本发明通过在相邻微通道之间的间隔功能区设置多孔热释电复合膜,使其能够响应冷凝液滴相变过程中释放的潜热产生瞬态极化电荷,并形成非均匀电场,无需外部电源即可为冷凝初期微液滴提供迁移驱动力,有利于提高冷凝界面的液滴更新能力,并降低系统能耗和结构复杂性。
Smart Images

Figure CN122900320A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of condensation strengthening and phase change heat transfer technology, specifically relating to a self-driven condensation strengthening surface based on pyroelectric effect and its preparation method. Background Technology
[0002] Currently, heat management devices based on the phase change heat transfer principle, such as heat pipes and vapor chambers, are widely used in the heat dissipation of electronic devices. Droplet condensation, as a highly efficient phase change heat transfer method, allows condensate droplets to continuously undergo dynamic processes such as nucleation, growth, coalescence, and detachment, compared to film condensation. This effectively reduces liquid film thermal resistance and significantly improves condensation heat transfer efficiency. However, under conditions of high heat flux density or horizontal placement, condensate droplets easily coalesce rapidly to form large droplets, even forming a continuous liquid film on the heat exchange surface. This increases liquid film thermal resistance and inhibits the continuous nucleation and growth of new droplets, making it difficult to maintain continuous renewal of the heat exchange surface, thus causing a significant decline in condensation heat transfer performance. Therefore, achieving rapid detachment and continuous renewal of condensate droplets, and reducing the liquid coverage of the heat exchange surface, is an important approach to achieving efficient droplet condensation and a key research direction in the field of condensation enhancement.
[0003] To improve the detachment efficiency of condensed droplets, existing technologies have primarily developed active driving methods. These methods utilize external excitations such as electric fields, magnetic fields, and mechanical vibrations to provide additional driving force to the condensed droplets, enabling droplet migration or detachment. For example, some Chinese invention patents employ electrowetting, electric field induction, or mechanical vibration to promote condensed droplet movement, which to some extent improves droplet renewal rate and condensation heat transfer performance. While these technologies can actively control droplet movement behavior, they typically require external driving power supplies, electrodes, or vibration devices. This not only increases system complexity but also raises operating energy consumption, making it difficult to meet the application requirements of compactness, high reliability, and low power consumption in fields such as electronic device heat dissipation, aerospace thermal control, and space phase change heat transfer.
[0004] To overcome the drawbacks of external power consumption and system complexity, recent research has gradually shifted towards passive driving strategies. The core of these strategies lies in inducing spontaneous droplet transport by meticulously constructing nanoscale surface topologies and introducing spatially non-uniform surface energy. Regarding the construction of condensation-enhanced interfaces, Chinese invention patent CN112229234A discloses a biomimetic condensation-enhanced heat transfer surface. By constructing gradient microchannels and hydrophilic nucleation regions, it aims to increase the nucleation density of condensed droplets and utilize the surface free energy gradient to promote droplet expulsion. Chinese invention patent CN109631611A discloses a hydrophobic substrate for enhanced condensation heat transfer, relying on micro / nano configurations to reduce the physical adhesion force of droplets at the solid-phase interface, thereby assisting in gravitational detachment.
[0005] To further enhance the autonomous transport capability of droplets, existing technologies propose constructing self-driven interfaces using wettability gradients, geometric gradients, and capillary pressure gradients. For example, Chinese invention patent CN105938300B constructs a gradient wetting surface, enabling droplets to achieve autonomous directional movement under the influence of surface energy gradients; Chinese invention patent CN108490736B utilizes shape gradients to establish Laplace pressure gradients, driving droplet autonomous transport solely through changes in microstructure geometry; and Chinese invention patent CN105820749B constructs a wedge-shaped geometric structure and a non-uniform wetting interface, utilizing the synergistic effect of Laplace pressure difference and wettability gradients to achieve directional transport of microdroplets. Furthermore, to reduce droplet movement resistance, slippery liquid-infused porous surfaces (SLIPS) are increasingly being applied in the field of condensation enhancement. These SLIPS form a stable liquid lubricant layer by storing lubricant in a micro / nano porous structure, reducing the contact resistance between the droplet and the solid surface and improving droplet slippage capability.
[0006] However, the aforementioned classic passive driving method reveals an insurmountable microscale self-driving blind zone problem when applied to high-intensity droplet condensation. Existing passive gradient self-driving condensation surfaces exhibit a significant "driving blind zone" defect. In the very early stages of droplet nucleation and growth (e.g., when droplet sizes are hundreds of micrometers or even micrometers), the droplet size is much smaller than the characteristic span of the asymmetric boundary or the transition region of the wetting gradient, preventing the droplet from reaching the non-uniform force boundary. Prolonged residence time in the blind zone directly accumulates significant thermal resistance, limiting further increases in the condensation heat transfer rate. On the other hand, while existing liquid lubricated surfaces (SLIPS) can effectively reduce droplet sliding resistance, they essentially only provide an inert, low-viscosity channel, lacking an active pumping and driving force for the very early nucleated microdroplets themselves.
[0007] Therefore, how to fully utilize the energy released during the condensation phase change without external energy input, endow the condensate droplets with migration ability in the early stage of nucleation, and work in synergy with subsequent geometric gradient driving to achieve continuous transport of condensate droplets from nucleation, growth to rapid detachment, is still of great research significance for further enhancing the heat transfer performance of droplet condensation. Summary of the Invention
[0008] The purpose of this invention is to address the problems of existing droplet condensation enhancement technologies, such as the reliance on external energy input and complex system structure in active-driven methods, and insufficient driving force in the early stages of condensation in passive-driven methods. This invention provides a self-driven condensation enhancement surface based on the pyroelectric effect and its preparation method. This enhanced surface utilizes the latent heat released during the phase transition of condensed droplets to trigger the pyroelectric effect, generating a driving force acting on the condensed microdroplets. This force synergizes with the gradient driving force formed by asymmetric microchannels, enabling continuous autonomous transport of condensed droplets from nucleation and growth to detachment, thereby improving the condensed droplet renewal capacity and condensation heat transfer performance.
[0009] To achieve the above objectives, the present invention adopts the following technical solution: A self-driven condensation-enhanced surface based on the pyroelectric effect includes a thermally conductive substrate. The surface of the thermally conductive substrate is provided with a plurality of asymmetric microchannels, and spacer functional regions are formed between adjacent asymmetric microchannels. A nanostructure is formed on the surface of the thermally conductive substrate. A pyroelectric composite film with a porous structure is provided on the surface of the spacer functional regions. Liquid lubricant is stored in the internal pores of the pyroelectric composite film, and a liquid lubricant layer is formed on its surface.
[0010] Preferably, the asymmetric microchannel is a gradient microchannel with a gradually changing channel width along the droplet transport direction to form a Laplace pressure gradient and promote the directional transport of condensed droplets.
[0011] Preferably, the pyroelectric composite membrane covers the spacer functional area, and the liquid lubricant is stably maintained within the porous structure of the pyroelectric composite membrane through capillary action, forming a continuous and stable liquid lubricant layer on the surface of the composite membrane.
[0012] During condensation, the latent heat of phase change released by the condensate droplets is transferred to the pyroelectric composite film, causing a change in the polarization state of the film and generating pyroelectric polarization, establishing an electric field near the interface formed between the film and the liquid lubricant layer. This electric field acts on the condensate droplets in the liquid lubricant layer, providing a driving force for the migration of the tiny droplets formed in the early stage of condensation, driving them to migrate towards adjacent asymmetric microchannels. Once the condensate droplets enter the asymmetric microchannels, they are further directionally transported and discharged under the influence of the Laplace pressure gradient formed by the channel geometry, thereby promoting the continuous detachment of the condensate droplets and surface renewal.
[0013] Preferably, the thermally conductive substrate is a metal substrate with good thermal conductivity.
[0014] Preferably, the metal substrate is selected from one of copper substrate, aluminum substrate, titanium substrate, stainless steel substrate, and nickel substrate.
[0015] Preferably, the asymmetric microchannel is formed by combining multiple geometrically asymmetric structures with gradually changing channel widths along the droplet transport direction to create a Laplace pressure gradient within the asymmetric microchannel, thereby driving the directional transport of condensed droplets.
[0016] Preferably, the pyroelectric composite film comprises a pyroelectric polymer and a matrix material.
[0017] Preferably, the pyroelectric polymer is selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer, and polyvinylidene fluoride-tetrafluoroethylene copolymer.
[0018] Preferably, the matrix material is selected from one or at least two of polydimethylsiloxane, polyurethane, polyimide, and epoxy resin.
[0019] Preferably, the liquid lubricant layer (5) comprises a hydrophilic lubricant layer or a hydrophobic lubricant layer; the hydrophilic lubricant layer is formed from one selected from ionic liquids and hydroxyl-terminated polydimethylsiloxanes; the hydrophobic lubricant layer is formed from one selected from perfluoropolyethers and dimethyl silicone oils with a kinematic viscosity of 10 cSt to 1000 cSt.
[0020] The present invention also provides a method for preparing the above-mentioned self-driven condensation-enhanced surface based on the pyroelectric effect, comprising the following steps: 1) Several asymmetric microchannels are fabricated on the surface of a thermally conductive substrate, and nanostructures are constructed on its surface; 2) The thermally conductive substrate is modified with low surface energy hydrophobicity; 3) Selectively forming porous pyroelectric composite membranes in the spacer functional regions between adjacent asymmetric microchannels; 4) Selectively treat the asymmetric microchannels to restore their hydrophilic properties and retain the surface structure of the pyroelectric composite membrane in the spacer functional area; 5) Inject liquid lubricant into the porous structure of the pyroelectric composite membrane to form a stable liquid lubricant layer on the surface of the composite membrane, thereby obtaining the self-driven condensation-enhanced surface based on the pyroelectric effect.
[0021] Preferably, the nanostructure includes one or at least two of CuO nanosheets, Cu2O nanocrystals, ZnO nanorods, and TiO2 nanostructures.
[0022] Preferably, the pyroelectric composite membrane (4) comprises polyvinylidene fluoride (PVDF) and polydimethylsiloxane (PDMS).
[0023] Preferably, the mass ratio of polyvinylidene fluoride to polydimethylsiloxane is 5:1 to 20:1.
[0024] Compared with the prior art, the present invention has the following beneficial effects: 1) This invention sets a porous pyroelectric composite membrane in the spacer functional area between adjacent microchannels, which can generate transient polarization charge in response to the latent heat released during the phase change of condensed droplets and form a non-uniform electric field. It can provide migration driving force for microdroplets in the early stage of condensation without the need for an external power source, which is beneficial to improve the droplet renewal capability of the condensation interface and reduce system energy consumption and structural complexity.
[0025] 2) This invention combines the electric field driving force generated by the pyroelectric effect with the low adhesion and low friction characteristics provided by the liquid lubricant layer, so that microdroplets can obtain migration driving force and undergo rapid sliding and coalescence in the early stage of condensation. This helps to shorten the residence time of microdroplets on the condensation surface, improve the problem of insufficient driving force in the early stage of condensation of traditional passive driving surfaces, and improve the renewal efficiency of condensed droplets.
[0026] 3) This invention utilizes asymmetric microchannels to achieve directional transport and rapid discharge of droplets after they enter the channels, leveraging the Laplace pressure gradient. This synergistic effect of pyroelectric and geometric gradient driving enables a continuous renewal process of condensed droplets from nucleation, growth, migration, coalescence, to detachment. This reduces droplet retention, maintains stable droplet condensation, and improves condensation heat transfer performance. Comparative results further demonstrate that pyroelectric driving alone is insufficient for continuous condensation enhancement; only the synergistic effect of pyroelectric driving and gradient transport in the asymmetric microchannels can achieve continuous droplet discharge and interface renewal.
[0027] 4) The present invention adopts a synergistic structure of pyroelectric composite membrane, porous liquid lubricant layer and asymmetric microchannel, which can effectively improve the problems of active drive relying on external energy input and passive drive having insufficient driving force in the early stage of condensation in the prior art. It provides a condensation enhancement interface that does not require external power supply for heat dissipation of electronic devices, heat pipes, heat spreaders and other phase change heat exchange devices.
[0028] 5) This invention utilizes the latent heat of phase change released by condensed droplets as a driving force source, realizing the in-situ utilization of energy released during the condensation process. This allows the self-driven migration of condensed droplets to occur synchronously with the condensation process, eliminating the need for an external power supply device and improving system integration and long-term operational reliability.
[0029] Finally, experimental results show that the condensation-enhanced surface constructed in this invention has high condensation droplet renewal capacity and condensation heat transfer performance. Under the same test conditions, compared with conventional hydrophilic super-slippery groove surfaces, the condensation rate is increased by about 23%, the large droplet retention phenomenon is significantly reduced, and a more stable droplet condensation state can be maintained.
[0030] The above-mentioned beneficial effects are the technical effects reflected in the preferred embodiments of the present invention. Those skilled in the art can make appropriate adjustments to the present invention according to actual application needs. Any product implementing the present invention does not necessarily have all of the above-mentioned beneficial effects at the same time. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the structure of the self-driven condensation-enhanced surface based on the pyroelectric effect of the present invention. Figure 2 This is a process flow diagram for preparing the self-driven condensation-enhanced surface based on the pyroelectric effect of the present invention; Figure 3 Microscopic morphology of the surface of pyroelectric composite films prepared with different PVDF to PDMS mass ratios; Figure 4 Comparison of infrared spectra of pyroelectric composite films prepared with different PVDF to PDMS mass ratios; Figure 5 Differential scanning calorimetry curves of porous pyroelectric composite membranes prepared with different PVDF to PDMS mass ratios; Figure 6 Comparison of crystallinity and β-phase content of porous pyroelectric composite membranes prepared with different PVDF to PDMS mass ratios; Figure 7 Transient output voltage response curves of pure PVDF film and pyroelectric composite film with PVDF to PDMS mass ratio of 10:1 under temperature change conditions; Figure 8 This is a comparison chart showing the cumulative condensate collection amount over time under horizontal placement conditions for both the example and the comparative examples. Figure 9 The following are comparison diagrams showing the droplet migration behavior and condensation state during the condensation process in the examples and comparative examples; Figure 10 This is a schematic diagram of the self-driven condensation enhancement mechanism based on the pyroelectric effect of the present invention.
[0032] Figure label: 1- Thermally conductive substrate; 2- Asymmetric microchannel; 3- Nanostructure; 4- Pyroelectric composite membrane; 5- Liquid lubricant layer. Detailed Implementation
[0033] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Various equivalent substitutions, improvements, or modifications made by those skilled in the art based on the technical concept of the present invention without departing from the spirit and scope of protection of the present invention should fall within the scope of protection of the present invention.
[0034] like Figure 1 As shown, the self-driven condensation-enhanced surface based on the pyroelectric effect of the present invention includes a thermally conductive substrate (1), an asymmetric microchannel (2) disposed on the surface of the thermally conductive substrate (1), a nanostructure (3) formed on the surface of the asymmetric microchannel (2), a porous pyroelectric composite membrane (4) disposed in the spacer functional areas between adjacent asymmetric microchannels (2), and a liquid lubricant layer (5) formed by liquid lubricant stored in the porous pyroelectric composite membrane (4). During the condensation process, the latent heat of phase change released by the condensed droplets excites the pyroelectric composite membrane (4) to generate a non-uniform electric field, which enables the microdroplets to obtain migration driving force in the early stage of condensation, and migrates to the asymmetric microchannel (2) under the low adhesion of the liquid lubricant layer (5), and then achieves directional transport and detachment under the action of the Laplace pressure gradient.
[0035] The present invention will be described below through different embodiments. Figure 2 As shown, the preparation process of the present invention includes steps such as microchannel fabrication, nanostructure construction, low surface energy modification, pyroelectric composite film preparation, selective plasma treatment, and liquid lubricant injection.
[0036] Example 1 This embodiment prepares a self-driven condensation-enhanced surface based on the pyroelectric effect, using a polar ionic liquid as a liquid lubricant. Its structure is as follows: Figure 1 As shown.
[0037] (1) Fabrication of thermally conductive substrates and construction of nanostructures The nanostructure is preferably composed of CuO / Cu2O nanosheets. A copper substrate with dimensions of 30 mm × 30 mm × 2 mm was selected as the thermally conductive substrate (1).
[0038] Several graded, gradually changing wedge-shaped grooves are machined on the surface of the thermally conductive substrate (1) to form asymmetric microchannels (2). The groove depth is 0.15 mm, and a spacer functional area with a width of 0.91 mm is formed between adjacent asymmetric microchannels (2).
[0039] The thermally conductive substrate (1) was then polished with 2000-grit sandpaper and ultrasonically cleaned in acetone, anhydrous ethanol and deionized water respectively. Each solution was ultrasonically cleaned for 10 minutes to remove surface oil and impurities.
[0040] The cleaned thermally conductive substrate (1) was immersed in a 2 mol / L hydrochloric acid solution for 10 s to remove the surface oxide layer, and then immersed in an alkaline reaction solution composed of 2.5 mol / L potassium hydroxide and 0.065 mol / L potassium persulfate. The reaction was carried out at 70℃ for 45 min to grow a nanostructure (3) composed of CuO / Cu2O on the surface of the asymmetric microchannel (2).
[0041] After the reaction is complete, rinse thoroughly with deionized water and dry.
[0042] Subsequently, the thermally conductive substrate (1) was placed in a sealed vacuum reaction vessel, and 120 μL of perfluorooctyltriethoxysilane (FAS) was added to the vessel. After evacuating to -0.10 MPa, the vessel was sealed and vapor-phase deposition was performed at 120 °C for 1 h, so that the thermally conductive substrate (1) as a whole formed a low surface energy modified layer.
[0043] (2) Preparation of pyroelectric composite membrane The pyroelectric polymer PVDF was dissolved in N,N-dimethylformamide (DMF) to prepare a PVDF solution with a mass fraction of 10%.
[0044] The matrix material PDMS was dissolved in ethyl acetate to prepare a PDMS solution with a mass fraction of 30%.
[0045] The two solutions were mixed at a solid-phase mass ratio of PVDF to PDMS of 10:1. The mixture was first ultrasonically dispersed for 10 min, and then mechanically stirred at 800 r / min for 20 min to obtain a uniform pyroelectric composite solution.
[0046] The thermally conductive substrate (1) is shielded by a slit mask plate, exposing only the spaced functional areas between adjacent asymmetric microchannels (2).
[0047] The pyroelectric composite liquid was uniformly coated onto the spacer functional area using a scraper, and the wet film thickness was controlled to be approximately 60 μm.
[0048] The sample was placed in a 35 ℃ forced-air drying oven for drying and curing, allowing DMF to slowly evaporate and form a porous structure inside the composite membrane, thereby obtaining a porous pyroelectric composite membrane (4).
[0049] (3) Selective surface treatment A porous pyroelectric composite membrane (4) is covered with a stainless steel mask plate corresponding to the spacer functional area, so that the spacer functional area is in a protected state and only the asymmetric microchannel (2) is exposed.
[0050] The sample was then placed in a plasma cleaner and treated for 2 minutes at 105 W radio frequency power in a mixed atmosphere of oxygen and argon.
[0051] After plasma treatment, the low surface energy modification layer on the surface of the asymmetric microchannel (2) is removed, restoring the superhydrophilic properties of the nanostructure (3), while the spacer functional region retains its original low surface energy state due to the mask protection.
[0052] (4) Construction of the liquid lubricant layer The preferred liquid lubricant is a 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (BMIm) ionic liquid. First, deionized water is filled into the asymmetric microchannel (2) to form a liquid barrier and prevent the subsequent liquid lubricant from entering the asymmetric microchannel (2).
[0053] Subsequently, polar ionic liquid BMIm was uniformly dropped onto the surface of the porous pyroelectric composite membrane (4).
[0054] Under capillary action, BMIm gradually penetrates into the pores inside the porous pyroelectric composite membrane (4) and is stored stably, forming a continuous liquid lubricant layer (5) on the surface of the composite membrane.
[0055] Finally, nitrogen purging is used to remove the deionized water from the asymmetric microchannel (2), thus obtaining the self-driven condensation-enhanced surface based on the pyroelectric effect described in this embodiment.
[0056] (5) Condensation process During the condensation process, water vapor preferentially condenses and nucleates on the surface of the liquid lubricant layer (5).
[0057] As the condensed droplets continue to grow, the latent heat of phase change they release is transferred to the porous pyroelectric composite membrane (4), which excites the pyroelectric composite membrane (4) to generate a non-uniform electric field, enabling the microdroplets to obtain migration driving force in the early stage of condensation.
[0058] The condensed droplets migrate to the adjacent asymmetric microchannel (2) on the low adhesion interface provided by the liquid lubricant layer (5). When the droplets enter the asymmetric microchannel (2), they are directionally transported along the channel direction and discharged from the condensation area under the action of the Laplace pressure gradient, thereby realizing the continuous renewal of the condensed droplets.
[0059] Description of this embodiment This embodiment uses a PVDF to PDMS mass ratio of 10:1 and employs the polar ionic liquid BMIm as the liquid lubricant, representing a preferred embodiment of the present invention. Experimental results show that this embodiment exhibits good pyroelectric response and droplet transport performance, and can serve as a control benchmark for subsequent embodiments and comparative examples.
[0060] Example 2 This embodiment provides a self-driven condensation-enhanced surface based on the pyroelectric effect with different spacing functional area sizes.
[0061] The difference between this embodiment and Embodiment 1 is that: The width of the spacer functional area between adjacent asymmetric microchannels (2) on the surface of the thermally conductive substrate (1) is 1.20 mm, and the other microchannel processing dimensions and nanostructure construction process are the same as in Example 1.
[0062] The remaining preparation steps are the same as in Example 1.
[0063] In the resulting condensation-enhanced surface, condensate droplets can nucleate on the surface of the pyroelectric composite film (4) and migrate to the asymmetric microchannel (2) under the combined action of the pyroelectric effect and the liquid lubricant layer, thus achieving directional transport.
[0064] Example 3 This embodiment provides a self-driven condensation-enhanced surface based on the pyroelectric effect, which has different pyroelectric composite film compositions.
[0065] The difference between this embodiment and Embodiment 1 is that: (1) The width of the spacer functional area between adjacent asymmetric microchannels (2) on the surface of the thermally conductive substrate (1) is kept at 0.91 mm.
[0066] (2) When preparing the pyroelectric composite membrane (4), the solid mass ratio of PVDF to PDMS was adjusted to 4:3, and the other preparation methods, coating processes and curing conditions were the same as in Example 1.
[0067] (3) Inject BMIm liquid lubricant into the porous pyroelectric composite membrane (4) to form a stable liquid lubricant layer (5) under capillary action.
[0068] The remaining preparation steps are the same as in Example 1.
[0069] In the resulting condensation-enhanced surface, the liquid lubricant layer has a low droplet slip resistance, which enables the migration and transport of condensed droplets to the asymmetric microchannel (2).
[0070] Example 4 This embodiment provides a self-driven condensation-enhanced surface based on the pyroelectric effect using dimethyl silicone oil as a liquid lubricant, to illustrate that the liquid lubricant described in this invention is not limited to ionic liquids.
[0071] The difference between this embodiment and Embodiment 1 is that: (1) The dimensions of the thermally conductive substrate (1), the structural dimensions of the asymmetric microchannel (2), the construction method of the nanostructure (3), and the low surface energy modification process are the same as in Example 1.
[0072] (2) When preparing the pyroelectric composite membrane (4), the solid mass ratio of PVDF to PDMS is maintained at 10:1. The preparation method, ultrasonic dispersion conditions, mechanical stirring conditions, selective coating process and curing conditions are the same as those in Example 1.
[0073] (3) The liquid lubricant used is dimethyl silicone oil with a kinematic viscosity of 100 cSt instead of the polar ionic liquid BMIm in Example 1.
[0074] The remaining preparation steps are the same as in Example 1.
[0075] The resulting condensation-enhanced surface can also utilize the pyroelectric composite film (4) to generate driving force in response to the latent heat of condensation, and combine with the liquid lubricant layer to reduce the resistance of droplet movement, so that the condensed droplets migrate to the asymmetric microchannel (2) and complete directional transport.
[0076] The above results show that the liquid lubricant of the present invention is not limited to ionic liquids. Any liquid lubricant that can be stably stored inside the porous pyroelectric composite membrane (4) and form a continuous liquid lubricant layer (5) can be used in the present invention.
[0077] Comparative Example 1 (Pyroelectric composite membrane) This comparative example illustrates the transport of condensed droplets without the pyroelectric composite membrane.
[0078] The difference between this comparative example and Example 1 is that the pyroelectric composite membrane (4) is not provided.
[0079] The specific preparation process is as follows: (1) A copper substrate with dimensions of 30 mm × 30 mm × 2 mm was selected as the thermally conductive substrate (1). A graded gradient wedge-shaped groove was formed on its surface as an asymmetric microchannel (2) according to the method of Example 1. The groove depth was 0.15 mm and the width of the functional area between adjacent asymmetric microchannels (2) was 0.91 mm.
[0080] (2) Mechanical polishing, ultrasonic cleaning, acid washing and deoxygenation and alkaline oxidation were performed in sequence according to the method of Example 1 to form a nanostructure (3) on the surface of the asymmetric microchannel (2).
[0081] (3) The thermally conductive substrate was modified with low surface energy using perfluorooctyltriethoxysilane (FAS).
[0082] (4) The spacer functional area is shielded by a mask plate, and only the asymmetric microchannel (2) is subjected to plasma treatment to restore the asymmetric microchannel to a superhydrophilic state, while the spacer functional area remains superhydrophobic.
[0083] (5) Subsequently, polar ionic liquid BMIm is uniformly dropped onto the surface of the porous pyroelectric composite membrane (4) to form a continuous liquid lubricant layer (5) on the surface of the composite membrane.
[0084] The condensation surface of the pyroelectric composite membrane is finally obtained.
[0085] During the condensation process, droplets mainly rely on the Laplace pressure gradient to enter the asymmetric microchannel. Due to the lack of pyroelectric driving force, microdroplets mainly rely on random aggregation before entering the microchannel in the early stage of condensation, resulting in a low droplet renewal rate.
[0086] Comparative Example 2 (without asymmetric microchannels) This comparative example illustrates the role of asymmetric microchannels in the directional transport of droplets.
[0087] The difference between this comparative example and Example 1 is that the thermally conductive substrate (1) maintains a planar structure and does not have asymmetric microchannels (2).
[0088] The specific preparation process is as follows: (1) A copper substrate with dimensions of 30 mm × 30 mm × 2 mm was selected as the heat-conducting substrate (1). Mechanical polishing, ultrasonic cleaning, acid pickling and deoxygenation and alkaline oxidation were performed in sequence to form a nanostructure on the substrate surface (3).
[0089] (2) The thermally conductive substrate is modified with low surface energy using FAS.
[0090] (3) A porous pyroelectric composite film is formed on the surface of the thermally conductive substrate according to the method of Example 1 (4).
[0091] (4) Inject BMIm into the porous pyroelectric composite membrane (4) to form a liquid lubricant layer (5) on the surface of the composite membrane.
[0092] The final result is a planar pyroelectric super-smooth condensation surface.
[0093] During the condensation process, the condensed droplets can migrate autonomously under the driving force of the electric field. However, due to the lack of a Laplace pressure gradient formed by asymmetric microchannels, the droplets are difficult to achieve continuous directional transport and rapid discharge.
[0094] Comparative Example 3 (PFPE Lubricant) This comparative example illustrates the effect of liquid lubricant polarity on the autonomous migration ability of condensed droplets.
[0095] The difference between this comparative example and Example 1 is that the structure and preparation process of the thermally conductive substrate (1), asymmetric microchannel (2), nanostructure (3) and pyroelectric composite membrane (4) are the same as those in Example 1, except that the liquid lubricant is replaced by hydrophobic perfluoropolyether (PFPE) instead of polar ionic liquid BMIm.
[0096] The specific preparation process is as follows: (1) A thermally conductive substrate (1), an asymmetric microchannel (2), a nanostructure (3), and a porous pyroelectric composite membrane (4) were prepared according to the method of Example 1.
[0097] (2) First, deionized water is injected into the asymmetric microchannel (2) to form a liquid barrier.
[0098] (3) Perfluoropolyether (PFPE) is uniformly dropped onto the surface of the porous pyroelectric composite membrane (4) and enters the pores inside the composite membrane by capillary action, forming a continuous liquid lubricant layer (5) on the surface of the composite membrane.
[0099] (4) Purge out the deionized water in the asymmetric microchannel (2) to obtain the PFPE lubricated pyroelectric condensation reinforced surface.
[0100] During the condensation process, PFPE can reduce the contact resistance between the droplets and the solid surface, giving the droplets better sliding properties; however, since PFPE is a non-polar liquid, the coupling effect with the electric field generated by the pyroelectric composite film is weak, and its effect on promoting the migration of microdroplets in the early stage of condensation is lower than that in Example 1.
[0101] Performance testing methods and results 1. Morphology and composition analysis of porous pyroelectric composite membranes (combined with...) Figure 3 and Figure 4 ) To verify the microstructure and chemical composition of the pyroelectric composite membrane (4) prepared in this invention, scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (ATR-FTIR) analysis were performed on PVDF-PDMS composite membranes with different ratios.
[0102] like Figure 3 As shown, the surface of the pure PVDF film has a uniformly distributed microporous structure, and there are abundant secondary pores inside the pore walls. When PDMS is introduced, the resulting PVDF-PDMS composite film still maintains a continuous multi-level microporous structure, with a slightly increased pore size and interconnected pores at each level. The above-mentioned porous structure is conducive to the penetration of liquid lubricant into the interior of the composite film under capillary action and its stable storage in the pores, thereby forming a continuous and stable liquid lubricant layer (5).
[0103] like Figure 4 As shown, the ATR-FTIR test results indicate that the pure PVDF membrane at 1405 cm⁻¹... -1 and 1181 cm -1 The characteristic absorption peak of PVDF appears at 1259 cm⁻¹; after the introduction of PDMS, the composite membrane shows an absorption peak at 1259 cm⁻¹. -1 and 1016 cm -1 Characteristic absorption peaks of Si-CH3 and Si-O-Si appeared at the respective locations, and the corresponding peak intensities gradually increased with the increase of PDMS content, indicating that PVDF and PDMS have successfully formed a composite structure.
[0104] The above results show that the PVDF-PDMS composite membrane used in this invention not only has a good porous structure, but also provides a stable storage space for liquid lubricants.
[0105] 2. Crystal structure analysis of pyroelectric composite films (combined with...) Figure 5 and Figure 6 ) To obtain a higher pyroelectric response, differential scanning calorimetry (DSC) and infrared spectroscopy were performed on PVDF-PDMS composite films with different ratios.
[0106] according to Figure 5 Based on the DSC test results, the crystallinity of PVDF is calculated using the following formula: ΔH m The enthalpy of melting of the sample, ΔH m 0 The theoretical enthalpy of fusion for 100% crystalline PVDF is 104.6 J·g. -1 .
[0107] like Figure 6 As shown, the calculation results indicate that the crystallinity of pure PVDF film, PVDF:PDMS mass ratios of 10:1, 2:1 and 4:3 are 63.1%, 63.8%, 51.5% and 52.3%, respectively.
[0108] Meanwhile, based on the ATR-FTIR test results, the relative content of the β phase in PVDF was calculated using the Lambert-Beer method: like Figure 6 As shown, the β-phase content of the pure PVDF film is 57.51%; when the mass ratio of PVDF to PDMS is 10:1, the β-phase content increases to 66.12%; when the mass ratios are 2:1 and 4:3, the β-phase content decreases to 61.32% and 57.74%, respectively.
[0109] The above results show that when the mass ratio of PVDF to PDMS is 10:1, the resulting composite film has both high crystallinity and β-phase content, and can obtain better pyroelectric performance. Therefore, the present invention preferably uses a PVDF:PDMS mass ratio of 10:1.
[0110] 3. Pyroelectric response performance testing (combined with...) Figure 7 ) To evaluate the response capability of the pyroelectric composite membrane of the present invention to temperature changes, transient temperature disturbance tests were conducted on pure PVDF membrane and PVDF-PDMS composite membranes with different ratios, and their output voltage was monitored in real time.
[0111] During the test, the local temperature fluctuations caused by the latent heat of condensation during the condensation process were simulated by periodic temperature changes, and the changes in the sample output voltage were recorded.
[0112] like Figure 7 As shown, the pure PVDF membrane generates a transient output voltage of approximately 386 mV during temperature changes; in contrast, the composite membrane with a PVDF:PDMS mass ratio of 10:1 used in Example 1 has a peak output voltage of 1009 mV, which is approximately 2.6 times that of the pure PVDF membrane.
[0113] The above results indicate that the appropriate introduction of PDMS can significantly improve the pyroelectric response capability of the pyroelectric composite membrane. Among them, the PVDF:PDMS mass ratio of 10:1 has good pyroelectric performance and can provide a stronger local electric field driving force for condensed droplets.
[0114] 4. Liquid lubricant layer wetting performance test To evaluate the wetting performance of different liquid lubricants after forming a liquid lubricant layer, the static water contact angle and sliding angle were measured for Examples 1, 4 and Comparative Example 3, respectively.
[0115] The test results are shown in Table 1.
[0116] Table 1 Wetting properties of different liquid lubricant layers Table 1 shows that the liquid lubricant layer formed using BMIm exhibits hydrophilic superlubricating properties, which is more conducive to the nucleation and migration of condensed droplets; while the liquid lubricant layer formed using PFPE and dimethyl silicone oil exhibits hydrophobic superlubricating properties, which can also reduce droplet movement resistance. These results demonstrate that the porous pyroelectric composite membrane of this invention can be adapted to different types of liquid lubricants and form a stable liquid lubricant layer.
[0117] 5. Condensation enhancement performance test (combined with) Figure 8 ) To verify the condensation enhancement effect of the present invention, continuous condensation tests were conducted on Examples 1-4 and Comparative Examples 1-3 under the conditions of ambient temperature 30 ℃, relative humidity 72%, condensation surface temperature 15 ℃ and horizontal placement.
[0118] like Figure 8 As shown, the cumulative condensate collection rates under horizontal placement conditions in the examples and comparative examples differed significantly over time. The test results are shown in Table 2.
[0119] Table 2 Comparison of condensation performance of various embodiments and comparative examples In Comparative Example 2, since no asymmetric microchannels were set up, although the condensate droplets could migrate autonomously to a certain extent, they could not form a continuous drainage path. Therefore, under horizontal placement conditions, the condensate could not continuously collect to the collection device, so the cumulative water collection volume was not counted.
[0120] As shown in Table 2, Example 1 has the highest condensate collection capacity, which is 23.0% higher than that of Comparative Example 1. Example 2 has a slightly reduced condensation performance due to its larger functional area width. Example 3 uses a pyroelectric composite membrane with a PVDF to PDMS ratio of 4:3, and its condensation effect is lower than that of Example 1. Example 4, using dimethyl silicone oil, also achieved better condensation performance than Comparative Example 1, indicating that the liquid lubricant described in this invention has a good applicability range.
[0121] Although Comparative Example 2 was able to drive local migration of droplets in the early stage of condensation through pyroelectricity, the droplets could not achieve continuous directional transport and discharge due to the lack of asymmetric microchannels to provide a Laplace pressure gradient. In the end, a large amount of droplets remained on the condensation surface and could not form a continuous liquid collection process. Therefore, no cumulative water collection statistics were performed. Comparative Example 3 used PFPE as a lubricant. Although it was able to form a stable liquid lubricant layer, the condensation enhancement effect was lower than that of Example 1, which used BMIm.
[0122] 6. Analysis of condensate droplet migration behavior (combined with...) Figure 9 ) To further analyze the influence of different structures on the migration behavior of condensed droplets, the condensation process of the examples and comparative examples was observed in real time under the same condensation conditions. The results are as follows: Figure 9 As shown.
[0123] Example 1 uses a porous pyroelectric composite membrane with a PVDF:PDMS mass ratio of 10:1, and injects BMIm inside to form a liquid lubricant layer. In the initial stage of condensation, condensate droplets can rapidly nucleate in the spacer functional regions and autonomously migrate towards adjacent asymmetric microchannels under the influence of the pyroelectric response induced by the latent heat of condensation. When the droplets contact the edge of the microchannel, they are rapidly captured and directionally transported along the channel under the influence of the Laplace pressure gradient within the microchannel, achieving continuous discharge of condensate droplets and maintaining a high renewal frequency at the condensation interface.
[0124] Example 2 retains the pyroelectric composite film (4) and the BMIm liquid lubricant layer (5), only increasing the width of the spacer functional area between adjacent asymmetric microchannels (2) on the surface of the thermally conductive substrate (1) from 0.91 mm to 1.20 mm. Due to the increased spacing between adjacent asymmetric microchannels (2), the distance required for condensed droplets to migrate to the edge of the microchannel within the spacer functional area increases accordingly. This reduces the efficiency of droplets entering the asymmetric microchannels (2), resulting in a decrease in the number of condensed droplets captured and directionally transported by the microchannels in a timely manner, and a decrease in the interface renewal rate. Therefore, its condensation enhancement effect is lower than that of Example 1.
[0125] Comparative Example 1 only has asymmetric microchannels and does not have a pyroelectric composite membrane. The condensed droplets mainly enter the microchannels by continuously growing and coalescing. In the early stage of condensation, the droplets stay in the interstitial area for a relatively long time, and a certain number of large droplets are still retained at the interface. The interface renewal rate is lower than that of Example 1.
[0126] Comparative Example 2 retained the pyroelectric composite membrane and BMIm liquid lubricant layer, but did not incorporate asymmetric microchannels. During the initial condensation phase, droplets could undergo some degree of autonomous migration and coalescence. However, due to the lack of directional capture and continuous transport paths provided by microchannels, the coalesced droplets ultimately remained on the condensation surface, making continuous drainage difficult. Under horizontal placement conditions, a stable condensate collection process could not be established.
[0127] comprehensive Figure 9 The results show that it is difficult to achieve continuous and efficient discharge of condensate droplets by relying solely on pyroelectric drive or solely on asymmetric microchannels. This invention, through the synergistic effect of porous pyroelectric composite membrane, liquid lubricant layer and asymmetric microchannels, enables condensate droplets to acquire autonomous migration ability in the early stage of nucleation, and achieves rapid capture and directional transport after reaching the microchannel, thereby forming a continuous condensate discharge process, effectively improving the renewal rate of the condensation interface and the condensation heat transfer performance.
[0128] 7. Analysis of the mechanism of self-driven condensation enhancement (combined with...) Figure 10 ) like Figure 10 As shown, during the condensation process, water vapor first nucleates on the surface of the liquid lubricant layer (5) and forms tiny droplets. The latent heat of phase change released by the condensed droplets is transferred to the porous pyroelectric composite membrane (4) below, inducing it to generate transient polarization charges and forming a local non-uniform electric field on the membrane surface.
[0129] Under the influence of a local electric field, the condensed droplets in the early stages of nucleation acquire a lateral driving force and migrate towards the adjacent asymmetric microchannel (2) with the help of the low interfacial resistance of the liquid lubricant layer. After entering the asymmetric microchannel (2), the droplets achieve rapid directional transport under the influence of the Laplace pressure gradient formed by the channel geometry and are eventually discharged from the condensation interface. If the condensation interface does not have an asymmetric microchannel (as in Comparative Example 2), although the droplets can migrate locally under the drive of the electric field, the lack of a continuous drainage channel causes the droplets to eventually coalesce and remain at the condensation interface, making it difficult to achieve continuous interface renewal.
[0130] Therefore, this invention realizes a continuous cycle process of condensed droplets from nucleation, self-driven migration, channel capture, directional transport to interface renewal, effectively improving the droplet renewal frequency and condensation heat exchange efficiency of the condensation interface.
Claims
1. A self-driven condensation-enhanced surface based on the pyroelectric effect, characterized in that, The system includes a thermally conductive substrate (1), the surface of which is processed with a plurality of asymmetric microchannels (2) and spacer functional regions located between adjacent asymmetric microchannels (2); the surface of the thermally conductive substrate (1) is provided with nanostructures (3); a porous pyroelectric composite film (4) is covered on the nanostructures on the surface of the spacer functional regions, and the pores of the porous pyroelectric composite film (4) are filled with liquid lubricant to form a liquid lubricant layer (5) in the spacer functional regions; the pyroelectric composite film (4) can generate pyroelectric polarization in response to temperature changes during the condensation process, and establish an electric field near the interface formed between it and the liquid lubricant layer (5). This electric field acts on the condensed droplets in the liquid lubricant layer to drive the condensed droplets on the liquid lubricant layer to migrate to the asymmetric microchannels (2), and cooperate with the Laplace pressure gradient formed by the asymmetric microchannels (2) to achieve directional transport of the condensed droplets.
2. The self-driven condensation-enhanced surface based on the pyroelectric effect according to claim 1, characterized in that: The thermally conductive substrate (1) is a metal substrate; the metal substrate is selected from one of copper substrate, aluminum substrate, titanium substrate, stainless steel substrate and nickel substrate.
3. The self-driven condensation-enhanced surface based on the pyroelectric effect according to claim 1, characterized in that: The asymmetric microchannel (2) is formed by combining multiple geometrically asymmetric structures with gradually changing channel widths along the droplet transport direction to form a Laplace pressure gradient within the asymmetric microchannel (2), driving the directional transport of condensed droplets.
4. The self-driven condensation-enhanced surface based on the pyroelectric effect according to claim 1, characterized in that: The pyroelectric composite membrane (4) includes a pyroelectric polymer and a matrix material; the pyroelectric polymer is selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer and polyvinylidene fluoride-tetrafluoroethylene copolymer; the matrix material is selected from one or at least two of polydimethylsiloxane, polyurethane, polyimide and epoxy resin.
5. The self-driven condensation-enhanced surface based on the pyroelectric effect according to claim 1, characterized in that: The liquid lubricant layer (5) is a hydrophilic lubricant layer or a hydrophobic lubricant layer; the hydrophilic lubricant layer is formed from one selected from ionic liquids and hydroxyl-terminated polydimethylsiloxanes; the hydrophobic lubricant layer is formed from one selected from perfluoropolyethers and dimethyl silicone oils with a kinematic viscosity of 10 cSt to 1000 cSt.
6. A method for preparing a self-driven condensation-strengthened surface based on the pyroelectric effect as described in any one of claims 1 to 5, characterized in that, Includes the following steps: 1) An asymmetric microchannel (2) with graded gradient wedge-shaped grooves is formed on the surface of a thermally conductive substrate (1); 2) Surface treatment is performed on the thermally conductive substrate (1) to construct nanostructures (3) on its surface; 3) Hydrophobic modification of the nanostructured thermally conductive substrate (1); 4) The pyroelectric polymer is mixed with the matrix material to prepare a pyroelectric composite liquid; 5) The pyroelectric composite liquid is selectively coated onto the spacer functional area between adjacent asymmetric microchannels (2), and after drying, a porous pyroelectric composite membrane (4) is formed. 6) The asymmetric microchannel (2) region is selectively treated using a mask combined with plasma treatment to restore its hydrophilicity; 7) Inject liquid lubricant into the pores of the porous pyroelectric composite membrane (4) to form a liquid lubricant layer (5), thereby obtaining the self-driven condensation-enhanced surface based on the pyroelectric effect.
7. The preparation method according to claim 6, characterized in that: In step 2), the nanostructure includes one or at least two of CuO nanosheets, Cu2O nanocrystals, ZnO nanorods, and TiO2 nanostructures.
8. The preparation method according to claim 6, characterized in that: In step 4), the pyroelectric polymer is polyvinylidene fluoride (PVDF), and the matrix material is polydimethylsiloxane (PDMS).
9. The preparation method according to claim 8, characterized in that: The mass ratio of polyvinylidene fluoride to polydimethylsiloxane is 5:1 to 20:1.
Citation Information
Patent Citations
A wedge-shaped non-uniform wettability surface capable of microdroplet self-transport and its preparation method
CN105820749B
Preparation method and device for realizing self-driven gradient wetting surface of droplets
CN105938300B
A functional layer for droplet self-driving based on shape gradient and its fabrication method
CN108490736B
Water repellent base plate, device and method for strengthening condensation heat exchange
CN109631611A
Bionic condensation enhanced heat transfer surface
CN112229234A